Absolute frequency metrology of the CHF3 8.6-µm ro-vibrational spectrum at 10−11 level. (June 2020) - Vicentini, Edoardo; Maddaloni, Pasquale; Aiello, Roberto; Gambetta, Alessio; Coluccelli, Nicola; Molteni, Lisa M.; Castrillo, Antonio; Gianfrani, Livio; De Natale, Paolo; Laporta, Paolo; Galzerano, Gianluca
Highlights: The absolute line center frequencies of 59 lines were measured with a fractional uncertainty ranging from 9 × 10 − 11 to 2 × 10 − 11, which represents a two-order-of-magnitude improvement with respect to our previous studies [A]. In addition, a detailed comparison with recent high-resolution FTIR measurements [B] was also accomplished, bringing out an enhancement in the accuracy performance by more than three orders of magnitude. Abstract: An optical-frequency-comb-referenced quantum cascade laser is used to perform wavelength-modulation Lamb-dip spectroscopy on a large number of ro-vibrational transitions falling in the CHF3 υ 5 fundamental band at 8.6 µm. The combined (statistical + systematic) fractional uncertainty in the absolute determination of the line-center frequencies ranges from 9 × 10 − 11 down to 2 × 10 − 11 . This represents an improvement by more than two orders of magnitude, as compared to a recent and extensive study performed with a high-resolution FTIR spectrometer [1]. Our investigation realizes a sharpened knowledge of the CHF3 spectrum over a wide interval, also managing to accurately determine the positions of very close, previously unresolved multiple ro-vibrational components.